2018
DOI: 10.17559/tv-20180419095119
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of CNC Grinding Process Parameters Using Different Neural Networks

Abstract: Continuation of research on solving the problem of estimation of CNC grinding process parameters of multi-layer ceramics is presented in the paper. Heuristic analysis of the process was used to define the attributes of influence on the grinding process and the research model was set. For the problem of prediction-estimation of the grinding process parameters the following networks were used in experimental work: Modular Neural Network (MNN), Radial Basis Function Neural Network (RBFNN), General Regression Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In order to imitate the nonlinear function, the network needs a neuron activation function. This transfer-activation function determines the moment of launching the impulse to the neuron network and it can be linear or nonlinear [21]. Guidelines or algorithms to select the proper number of neurons do not exist.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to imitate the nonlinear function, the network needs a neuron activation function. This transfer-activation function determines the moment of launching the impulse to the neuron network and it can be linear or nonlinear [21]. Guidelines or algorithms to select the proper number of neurons do not exist.…”
Section: Artificial Neural Networkmentioning
confidence: 99%
“…They concluded that the RSM provided a better prediction of surface roughness. Paper [13] represents the comparative study that used different neural networks to estimate the process parameters during grinding.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [27][28][29][30] were using the Root Mean Square Error (RMSE) as a criterion for evaluating the model. The disadvantage of quality measures used by squaring the individual error due to which higher values of individual error take a larger share in the overall results and thus give greater importance to greater deviations [31].…”
Section: System Optimization Using a Neural Networkmentioning
confidence: 99%
“…The proposed system also included, among others, prediction of surface roughness by cutting parameters and control of obtained or needed surface roughness by means of the characteristics quantified from the digital image of the observed machined surface. Authors [22,23] use various algorithms of neural networks for investigation of manufacturing problems.…”
Section: Introductionmentioning
confidence: 99%